“Interested parties” versus unlawful State aid. State of play in CJEU’s caselaw - Agata Jurkowska-Gomulka; Artur Salbert (Market and Competition Law Review)
In case of unlawful State aid, Art. 24(2) of Regulation 2015/1589 guarantees the possibility to submit a complaint to “any interested party”. The preamble to Regulation 2015/1589 even encourages the submission of such claims. Interested parties are defined by Art. 1(h) of this Regulation as “any Member State and any person, undertaking or association of undertakings whose interests might be affected by the granting of aid, in particular the beneficiary of the aid, competing undertakings and trade associations”. The fact that an entity belongs to one of the categories indicated in this provision (e.g., beneficiary or trade associations) does not determine its status of interested party – a key factor is proving that the interests of a particular entity have been affected by the (potentially) unlawful aid. The concept has been developed in case law. Among many detailed issues in judgements delivered either on the basis of Regulation 2015/1589 or the preceding Regulation 659/1999, the CJEU has discussed conditions under which a status of interested party could be attributed to undertakings in no direct competition with a recipient of State aid. Special attention is drawn to a beneficiary of State aid as a potential “interested party” – this category of entities is mentioned in Art. 1(h) of Regulation 2015/1589, but a form that needs to be used in order to submit a complaint does not list a beneficiary as a subject entitled to submitting a complaint. The article presents a review of CJEU cases in this regard, and aims at defining the current state of interpretation of “interested party” that opens a gate for particular entities to submit a complaint.